2012
DOI: 10.3892/ijo.2012.1727
|View full text |Cite
|
Sign up to set email alerts
|

p63 regulates cell proliferation and cell cycle progression-associated genes in stromal cells of giant cell tumor of the bone

Abstract: Giant cell tumor of bone (GCT) is a destructive neoplasm of uncertain etiology that affects the epiphyseal ends of long bones in young adults. GCT stromal cells (GCTSCs) are the primary neoplastic cells of this tumor and are the only proliferating cell component in long-term culture, which recruits osteoclast-like giant cells that eventually mediate bone destruction. The oncogenesis of GCT and factors driving the neoplastic stromal cells to proliferate extensively and pause at an early differentiation stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The role of p63 in GCTB oncogenesis is unknown. Recently Lau et al showed that p63 regulates tumour cell proliferation in GCTB by binding to CDC2 and CDC25C [24]. Further studies are required to unravel the function of p63-phenotypic, oncogenic or tumour suppressive-in GCTB.…”
Section: Resultsmentioning
confidence: 97%
“…The role of p63 in GCTB oncogenesis is unknown. Recently Lau et al showed that p63 regulates tumour cell proliferation in GCTB by binding to CDC2 and CDC25C [24]. Further studies are required to unravel the function of p63-phenotypic, oncogenic or tumour suppressive-in GCTB.…”
Section: Resultsmentioning
confidence: 97%
“…, Lau et al . , Shooshtarizadeh et al . ), as well as in neoplastic lymphocytes in patients with non‐Hodgkin's lymphoma (Hedvat et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that mutations in p53 are correlated with the lung metastasis in GCTB [13]. In addition, the overexpression of p63 has been implicated in GCTB progression [14]. Thus, these proteins might play a regulatory role in the progression of GCTB.…”
Section: Introductionmentioning
confidence: 99%